The very hungry caterpillar finger puppet book - Carle, Eric (Puffin Books London, 2010)
Suitable for babies and toddlers, this picture book features a plush caterpillar finger puppet that wriggles his way through the holes in each page, munching and crunching through foods before transforming into a butterfly